2005
DOI: 10.1002/mrd.20279
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of telomere length and telomerase activity in cloned pigs and cows

Abstract: Inefficiency in the production of cloned animals is most likely due to epigenetic reprogramming errors after somatic cell nuclear transfer (SCNT). In order to investigate whether nuclear reprogramming restores cellular age of donor cells after SCNT, we measured telomere length and telomerase activity in cloned pigs and cattle. In normal pigs and cattle, the mean telomere length was decreased with biological aging. In cloned or transgenic cloned piglets, the mean telomere length was elongated compared to nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…Although porcine embryos from somatic cell nuclear transfer acquire a typical methylation pattern as control embryos and have normal telomere length (Jeon et al 2005;Kang et al 2001b), they display sporatic dysregulation of genes that are critical to embryo development (Lee et al 2004;Miyazaki et al 2005). This is consistent with the widely reported abnormal gene expression in mouse and bovine NT embryos (Bortvin et al 2003;Daniels et al 2000;Han et al 2003;Mann et al 2003;Wrenzycki et al 2002;Wrenzycki et al 2001).…”
Section: Discussionmentioning
confidence: 62%
“…Although porcine embryos from somatic cell nuclear transfer acquire a typical methylation pattern as control embryos and have normal telomere length (Jeon et al 2005;Kang et al 2001b), they display sporatic dysregulation of genes that are critical to embryo development (Lee et al 2004;Miyazaki et al 2005). This is consistent with the widely reported abnormal gene expression in mouse and bovine NT embryos (Bortvin et al 2003;Daniels et al 2000;Han et al 2003;Mann et al 2003;Wrenzycki et al 2002;Wrenzycki et al 2001).…”
Section: Discussionmentioning
confidence: 62%
“…We found relatively high levels of telomerase expression in both in vivo and in vitro-produced blastocysts. Relatively high levels of telomerase activity were previously described in porcine and bovine blastocysts derived in vitro and in vivo [36][37][38]. The samples used for telomerase expression assessment in our blastocyst-derived cell lines were collected during culture passaging.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, however, the vast majority of cloning studies reported that telomere length in cloned cattle, pigs, goats and mice are comparable with age-matched, naturally bred controls even when senescent donor cells were used for cloning (Jiang et al 2004, Betts et al 2005, Jeon et al 2005, Schaetzlein & Rudolph 2005. The regulation of telomere length is to some extent related to the type of donor cells employed for cloning.…”
Section: Telomere Length and Somatic Cloningmentioning
confidence: 99%